Dinamika Jamaah Ahmadiyah Indonesia (JAI) Qadian di Bali 1953-2013 - Mukhsen, Zainul; Dewi Setiowati Sunaryo, Fransiska (Humanis; Vol 18 No 1 (2017), 2017)
This thesis discussed about Jamaah Ahmadiyah Indonesia (JAI) of Qadian in Bali, a group of religious tenet which obey the doctrines  and guidances of Mirza Ghulam Ahmad. This Jamaat was established on March 23, 1889 in India. Ahmadiyah had entered Indonesia since 1925 in Tapak Tuan western coast of Aceh. Ahmadiyya is divided into two, Ahmadiyya Qadian and Lahore. Both of these groups have their own organizations in Indonesia. The Lahore Ahmadiyya group calls itself Indonesian Ahmadiyah Movement, where as Ahmadiyya Qadian namely Jamaah Ahmadiyah Indonesia. Jamaah Ahmadiyah Indonesia successfully develop and establish their center in Bogor, mean while the Indonesian Ahmadiyah Movement centered in Yogyakarta and their development is so rapid because the organization is not tight. Jamaah Ahmadiyah Indonesia (JAI) of Qadian in Bali first entered to Bali (at that time Bali was the part of Nusa Tenggara province) carried by Min. Idris in Singaraja in 1953. Ahmadiyya Community Center in Bali consists of three subdivisions, they are Denpasar, Singaraja and Penyabangan subdivisions. The study of Jamaah Ahmadiyah Indonesia (JAI) of Qadian in Bali seeks to examine the focus of several problems (1) How the development of Jamaah Ahmadiyah Indonesia (JAI) of Qadian in Bali from 1953-2013. (2) Why is the tenet doctrines in Jamaah Ahmadiyah Indonesia (JAI) of Qadian in Bali is different from other Islamic sects, in terms of prophecy, apocalypse, Al-Masih and Al-Mahdi, and the Tadzkirah scripture (3) How does the relationship between Indonesian Ahmadiyya Qadian in Bali with non-Ahmadiyah from 1953 to 2013.
Keywords: Jamaah Ahmadiyah, Qadian, and Bali.